Задача Коші для диференціальних рівнянь вищих порядків у банаховому просторі - Горбачук, М.Л.; Горбачук, В.І. (Видавничий дім "Академперіодика" НАН України, 2008)
The solutions to an abstract m-harmonic equation on (0,∞) are described. The necessary and sufficient conditions on initial data, under which the Cauchy problem for such an equation is solvable in the class of finite-order and finite-type entire vector-valued functions for a dense set of initial data, are presented.